Defensive Compounds Involved in the Invasiveness of Tithonia diversifolia - Hisashi Kato-Noguchi; Midori Kato (Molecules)
Tithonia diversifolia (Hemsl.) A. Gray forms high-density impenetrable monospecific stands as an invasive plant species. Its life history traits, such as high adaptability with high genetic variation under different environmental conditions, and high growth and reproductive capacity, may contribute to its success in invading and increasing its population in the introduced ranges. Evidence has accumulated in the literature for the activity of compounds involved in the invasive characteristics of Tithonia diversifolia against natural enemies such as herbivorous insects and mammals, pathogenic nematodes, fungi, and viruses, and of allelochemicals against neighboring competitive plant species. Tagitinin A, tagitinin C, 1β-methoxydiversifolin, phytol, phytol acetate, α-pinene, bicyclo[3.1.0]hexane,4-methylene-1-(1-methylethyl), hispidulin, dihydro-p-coumaric acid, and methyl linoleate are toxic to herbivorous insects, and tagitinin C and 5-O-(E)-caffeoylquinic acid are harmful to herbivorous mammals. Tirotundin has nematocidal activity. α-Pinene, camphor, eucalyptol, and α-terpineol have fungicidal activity. Tagitinin A, tagitinin C, and 1β-methoxydiversifolin-3-O-methyl ether have antiviral activity. Tagitinin A, tagitinin C, 1β-methoxydiversifolin, and hispidulin act as allelochemicals that inhibit the growth of neighboring competing plant species. The ability to outcompete natural enemies and competing plant species is one of the essential factors for infestation and increase in the population and distribution of Tithonia diversifolia in new habitats. Therefore, these compounds may be involved in the invasive characteristics of Tithonia diversifolia. This is the first review article focusing on the compounds involved in the invasive characteristics of Tithonia diversifolia.